(untitled) (SAARC Journal of Agriculture, 2026)
Developing agricultural manpower, for the scientists in 13 research institutes within the National Agricultural Research and Extension System (NARES) of Bangladesh together with associated agencies under the supporting ministries is essential for sustainable technology generation and adoption. They often operate with limited skills and expertise. In order to address the issue, the Government of Bangladesh undertook a signature PhD program under the National Agricultural Technology Program Phase II (NATP-2) awarding 140 fellowships, 80 in-country and 60 overseas. The NATP-2 PhD program started in 2018 and passed through the COVID-19 pandemic facing severe academic disruptions. A survey was conducted via email among the awardees during January-March 2021 to assess the impact of the pandemic on academic courses research, as well as the measures undertaken to adapt to the unprecedented stress. The results indicate that awardees at both in-country studied and international overseas universities faced disruptions in their mandatory academic courses and research. Most of the fellows required extension of the PhD program duration up to 6 months. In addition to change in schedule, extra funding also required which was allocated case-by-case. Through those coping mechanisms, on one hand, the NATP-2 PhD program successfully completed, on the other, agencies of the awardees lost access to their services. SAARC J. Agric., 23(2): 191-202 (2025)